Potentials and pitfalls of clinical peptidomics and metabolomics (Swiss Medical Weekly, 2013)
Clinical peptidomics and metabolomics are two emerging “-omics” technologies with the potential not only to detect disease-specific markers, but also to give insight into the disease dependency of degradation processes and metabolic pathway alterations. However, despite their rapid evolution and major investments, a clinical breakthrough, such as the approval of a major cancer biomarker, is still out of sight. What are the reasons for this failure? In this review we focus on three important factors: sensitivity, specificity and the avoidance of bias. The way to clinical implementation of peptidomics and metabolomics is still hampered by many of the problems that had to be solved for genomics and proteomics in the past, as well as new ones that require the creation of new analytic, computational and interpretative techniques. The greatest challenge, however, will be the integration of information from different “-omics” subdisciplines into straightforward answers to clinical questions, for example, in the form of new, superior “meta-markers”.